Transmission Performance Analysis of WDM Radio over Fiber Technology for Next Generation Long-Haul Optical Networks - Badiaa Ait Ahmed; Otman Aghzout; Mounia Chakkour; Fahd Chaoui; Azzeddin Naghar (International Journal of Optics)
This paper presents a detailed study of N-channels Wavelength Division Multiplexing (WDM) Optical transmission system using Radio over Fiber (RoF) technology. The study was applied to optical long-haul networks to overcome the nonlinearity effects, chromatic dispersion, and signal loss. For this purpose, Fiber Bragg Grating (FBG) has been implemented in 4-channels, 8-channels, and 16 channels WDM transmission system network at 10 Gb/s to compensate the dispersion and the nonlinear distortion. The use of erbium-doped fiber amplifiers (EDFA) has been also investigated to improve the quality of the transmission system. In Digital RoF, the impact analysis of modulation types such as Differential Phase-Shift Keying (DPSK) and Quadrature Amplitude Modulation (QAM) is also introduced. Constellation diagrams, received optical power, types of modulation, fiber dispersion, channel spacing variation, and laser power were considered to validate the study with the existing studies. All results achieve good reliability performance and prove the efficiency of the presented model.